Gabriela Mistral and Italy (Iter, 2022)
W uith admiration Gabriela Mistralpraises and evalúes the art, literature and religión of Medieval andRenaissance Italy; centering it in Florence. She points out its aesthehtic,ethic and religious traits, which have Consolidated herown poetic creed.